2020
DOI: 10.26550/2209-1092.1080
|View full text |Cite
|
Sign up to set email alerts
|

The Perioperative Nurse Surgical Assitant (PNSA) of the future

Abstract: Advanced practice nurse (APN) roles have been implemented across all areas of the Australian health service and have extended into the perioperative environment in the form of the perioperative nurse surgical assistant (PNSA) or non-medical surgical assistant (NMSA). With a growing and ageing population, Australia will see an increased demand for acute care nurses. For the PNSA role to expand to meet this demand, the role requires recognition and regulation in Australia. Education programs also need to meet th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The potential barriers to perioperative nurses becoming PNSAs was explored in the research to identify future potential workforce shortfalls, due to a projected increased demand for surgical services. 23,29 PNSAs contribute to the provision of surgical service delivery in rural public health services, where demonstrated doctor shortages exist and advanced practice nurses are required to meet future service demand. 2,23 With barriers to perioperative nurses pursuing the role of PNSA in Australia; however, and ongoing obstacles relating to professional recognition and accredited remuneration pathways for PNSAs, an expanding PNSA workforce or broader scope of practice for improved surgical patient care is improbable in the imminent future, and a challenge for the distant future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential barriers to perioperative nurses becoming PNSAs was explored in the research to identify future potential workforce shortfalls, due to a projected increased demand for surgical services. 23,29 PNSAs contribute to the provision of surgical service delivery in rural public health services, where demonstrated doctor shortages exist and advanced practice nurses are required to meet future service demand. 2,23 With barriers to perioperative nurses pursuing the role of PNSA in Australia; however, and ongoing obstacles relating to professional recognition and accredited remuneration pathways for PNSAs, an expanding PNSA workforce or broader scope of practice for improved surgical patient care is improbable in the imminent future, and a challenge for the distant future.…”
Section: Discussionmentioning
confidence: 99%
“…What this paper adds • The knowledge, skills and qualities of the PNSA provide a nexus within the operating team, with the surgeons they assist and to develop a positive culture with the surgical environment. 16,23 Studies into the role of the PNSA have identified multiple patient-centred benefits throughout the phases of perioperative care; preoperative, intraoperative and postoperative. 2,4,5,7,8,13,18,26,27 Such benefits relate to the areas of leadership, educational resource, patient education, operating theatre efficiency, reduction of surgical site infection, patient advocacy, knowledge of anatomy, instrumentation, equipment and surgical procedures, and collaboration between professional, medical and allied health groups.…”
Section: What Is Already Known About the Topic?mentioning
confidence: 99%
See 1 more Smart Citation